The Formative Determinants of Intellectual Capital in Jordanian Universities - Karadsheh, Munir; Al-Khatatneh, Abdul Khaleq; Al-Azzam, Abdul Baset (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to identify the demographic, social, economic, and academic determinants of intellectual capital formation among academics in Jordanian universities. Methods: Depending on the descriptive analytical approach, the study used a questionnaire as the measurement tool to collect data. The questionnaire was prepared specifically for this purpose and was distributed among a sample of 600 academic researchers. The study tool is based on the descriptive analytic method by using the multivariate regression. Results: The results of the study show that the complicated procedures for publishing, evaluating, and supporting scientific research, the limited number of specialized scientific journals, the weak capacities of scientific researchers, and the excessive teaching workload have posed challenges to scientific production. The results also revealed that there are statistically significant differences in the high number of refereed or published scientific research among members of the sample in favor of males, small-scale families, Ph.D. holders, natural science professionals, and academics with professorship, long experience, and high income. "Years of experience" is the most important variable that explains the discrepancy in the number of scientific research of academics, followed by the "academic rank," "gender," "monthly income level," "type of college or specialization," and finally, "the academic institution." Conclusions: The study recommends that Jordanian academic institutions should place scientific research at the top of their priorities and support academics materially and morally in accordance with precise and deliberate scientific strategies.